Analysis of stiffened and unstiffened slabs. - Bhalla, D. S. B. (University of Ottawa (Canada), 1972)
High Precision Finite elements have been used to determine displacements and internal forces of rectangular and skewed slabs. The displacement model is derived on the assumptions of small deflection theory and the principles of linear elasticity. The high precision triangular plate bending element with six degrees of freedom per node, developed by Cowper, Lindberg, Olson & Kosko has been used to study the behaviour of slabs under concentrated loads. A computer program is developed for the generation of the stiffness maxtrix of the individual elements. These matrices are used to represent the structure force-displacement relationships. To widen the scope of study, linear elastic members are incorporated and some problems of stiffened slabs are analysed. A compatible beam element is developed to represent the stiffeners. In the case of eccentric stiffeners in-plane forces are developed. To take the in-plane forces into account a complete cubic function is assumed for the tangential displacements. Comparisons with the existing solutions are made to establish the accuracy achieved on using high precision elements.
Keywords: Engineering, Civil.